2015
DOI: 10.1111/acer.12773
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of 6 Standard Rodent Diets on Binge-Like and Voluntary Ethanol Consumption in Male C57BL/6J Mice

Abstract: Background In recent years much attention has been given to the lack of reproducibility in biomedical research, particularly in pre-clinical animal studies. This is a problem that also plagues the alcohol research field, particularly in consistent consumption in animal models of alcohol use disorders. One often overlooked factor that could affect reproducibility is the maintenance diet used in pre-clinical studies. Methods Herein, two well-established models of alcohol consumption, the “drinking in the dark”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 45 publications
1
43
2
Order By: Relevance
“…Mice were housed individually in an AALAC accredited vivarium maintained at 22° C with a reversed 12:12 hour light:dark cycle. Mice had ad libitum access to either Prolab® RMH 3000 (Purina LabDiet®; St. Louis, MO) or Teklad Diet® 2920X (Harlan Laboratories Inc.; Indianapolis, IN) and water, unless otherwise stated (Marshall et al 2015). Prior to any experimental procedures, animals were allotted at least a week to fully acclimate to the environment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice were housed individually in an AALAC accredited vivarium maintained at 22° C with a reversed 12:12 hour light:dark cycle. Mice had ad libitum access to either Prolab® RMH 3000 (Purina LabDiet®; St. Louis, MO) or Teklad Diet® 2920X (Harlan Laboratories Inc.; Indianapolis, IN) and water, unless otherwise stated (Marshall et al 2015). Prior to any experimental procedures, animals were allotted at least a week to fully acclimate to the environment.…”
Section: Methodsmentioning
confidence: 99%
“…Binge drinking was modeled using a 4 day DID paradigm exactly as previously described (Marshall et al 2015; Rhodes et al 2005). Three hours into the dark cycle, home cage water bottles were removed and replaced with a single sipper tube container.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the relationship between HFD consumption and alcohol intake could be dependent on the presence or absence of dietary manipulations while alcohol testing occurred [62], raising the necessity of testing alcohol drinking at multiple times following palatable diets exposure. A relatively recent study showed that alcohol drinking behavior in rodents could be differentially impacted in mice maintained on various standard rodents chows [63]. This study not only helps to address some of the discrepancies in the HFD-induced alterations in alcohol drinking mentioned above but also raises an important point on experimental design while assessing the impact of various dietary manipulations.…”
Section: Non-human Studiesmentioning
confidence: 78%
“…In addition, alcohol intake and preference of control mice were at a similar level to what was reported by Blednov et al (2011) for male C57BL/6J mice. Although these parameters were closely similar, many factors, including microbiological status of animals, rodent diet used (Marshall et al, 2015), and our use of individually ventilated cages can modulate consequences of LPS challenge, producing the lack of expected enhancing effect on alcohol intake. For example, a recent study indicates a strong impact of microbiological status of animal husbandry on the mouse immune system (Beura et al, 2016).…”
Section: Discussionmentioning
confidence: 89%